The use of hydrophilic carrier derived from eggshell and novel gel forming technique in a solid dispersion system - Zarni Myint; Pojawon Prayurnprohm Lawanprasert; Satit Puttipipatkhachorn; Jiraporn Leanpolchareanchai (Faculty of Pharmacy, Mahidol University, 2023)
The study aimed to prepare calcium acetate (CaA) from the eggshell (ES) by the chemical reaction with aqueous acetic acid and to improve the dissolution properties of poorly soluble model drug, chloroxylenol (CXN), by solid dispersion (SD) system with CaA as a carrier. In the present study, SDs were prepared by two methods using various drug:carrier ratios. Fourier-transform infrared spectroscopy (FTIR), powder X-ray diffraction (PXRD), thermal analysis and scanning electron microscope (SEM) studies were carried out to characterize the prepared SDs in comparison with pure drug and physical mixtures (PMs). FTIR analysis indicated that there was an intermolecular hydrogen bonding between the terminal hydroxyl group of drug and water molecules of CaA. Decrease in crystallinity of SDs was observed in PXRD and differential scanning calorimetry (DSC) studies. Moreover, thermogravimetric analysis (TGA) study showed the drug protected within SD. SEM images revealed the morphology of SDs prepared by the gel forming technique as a rod-like microstructure in which the drug was occupied. The rough surface of SD prepared by the wet granulation method was due to the adherence of drug particles on the surface of CaA. SDs prepared by the gel method exhibited superior performance for the dissolution of CXN with a release of 93-113% at 60 min compared to PMs and pure CXN, which could be due to its transformation from crystalline to amorphous form as well as the improved wettability. Therefore, CaA might be the potential candidate for the dissolution enhancement of poorly soluble drugs.